STRATEGY ON SUSTAINABLE LIVELIHOOD COMMUNITY AFTER IMPLEMENTATION CONSERVATION PARTNERSHIP IN NATIONAL PARKS BANTIMURUNG-BULUSARAUNG - Mudrika Qanitha; Hardjanto Hardjanto; Leti Sundawati (Media Konservasi, 2023)
The livelihood system is an effort to make a living carried out by an individual or household to live by utilizing the resources they have. From the change in the status of the area, namely from a protected forest to a national park, the community experienced a decline in the livelihood system so the government issued a program for community empowerment as well as forest area conservation through a conservation partnership permit. The purpose of this study is to analyze sustainable livelihood strategies based on available assets or capital. This research method uses qualitative and quantitative analysis through 3 stages, namely the input stage, the matching stage, and the decision stage. The results showed that from the conservation partnership villages, namely Labuaja, Rompegading, Barugae, Patanyamang, Mattampawalie, Patanyamang and Wanua Waru, had the highest assets and capital. From the analysis of internal and external factors, the most influential on this livelihood system is the external factor with a score of 4.26. After analyzing these factors, the SWOT analysis shows that the community's livelihood system is in the Growth-Oriented Strategy (Quadrant I). QSPM analysis shows that the four emerging strategies are survival strategy, consolidation, and accumulation and shows that the highest strategy with a score of 0.72 is the running strategy. The conclusion is that the sustainable livelihood strategy that is considered the most capable of improving the community's livelihood system in this conservation partnership permit is a strategy.